Studi Kasus Pasien Dengan Meningitis Tuberkulosis Dalam Pengobatan Tuberkulosis Paru - Riduan Benny Nahampun; Helny Tarigan (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
TB meningitis is the most severe manifestation of tuberculosis infection and causes death and disability in 50% of sufferers. Tuberculosis primarily affects adults at their most productive ages. However, all age groups remain at risk. Tuberculous meningitis is a form of extra-pulmonary tuberculosis with neurological abnormalities that accounts for 70-80% of all neurological tuberculosis cases, 5.2% of all extrapulmonary tuberculosis and 0.7% of all tuberculosis cases. Tuberculous meningitis (TB) is preceded by prodromal symptoms such as headache, anorexia, nausea/vomiting, subfebrile fever, accompanied by behavioural changes, and decreased consciousness. The patient, a 42-year-old male Mr SM, presented with decreased consciousness, a history of seizures and was taking tuberculosis drugs. Meningeal stimulation was found to be rigid, laseque test and kernique test were positive. Motor system impression of lateralisation to the right. Laboratory examination showed leukocytes 13,500/uL, platelets 728,000/uL, sodium 123 mmol, Kgd 135, thoracic X-ray with the impression of pulmonary tuberculosis with pneumonia, cranial CT-scan obtained with the impression of appropriate Tb meningitis, Non Communicating hydrocephalus. Specific treatments given were IVFD NaCL 0.9 % 20 drops / m, Omeprazole vial 2x40 mg, paracetamol infusion 3x1000 mg, Ceftriaxone 1 gram Vial, dexamethason ampoule loading 2 ampoules then 3x5 mg, Phenytoin 3x100 mg, Levofloxacin 750 mg, rifampicin 1x450 mg, isoniazid 1x300 mg, pyrazinamide 1x1000 mg, ethambutol 1x1000 mg, mg, B6 and B12 2x1 tablets.